Dual C–H functionalization of N-aryl tetrahydroisoquinolines: a highly diastereoselective synthesis of dibenzo[a, f]quinolizines via visible-light induced oxidation and inverse electron-demand aza-Diels–Alder reaction. Issue 6 (25th November 2015) - Xu, Guo-Qiang; Li, Chen-Guang; Liu, Ming-Qian; Cao, Jian; Luo, Yong-Chun; Xu, Peng-Fei
Abstract : Dual C–H functionalization of amines with high diastereoselectivity is developed via visible-light photocatalysis and inverse electron-demand aza-Diels–Alder reaction. Abstract : Described herein is the first example of the application of an iminium intermediate generated by visible-light photocatalyzed oxidation in an inverse electron-demand aza-Diels–Alder reaction. This dual functionalization of both C(sp 3 )–H and C(sp 2 )–H bonds of N -aryl tetrahydroisoquinolines represents a valuable example for access to polycycles with high diastereoselectivity.